Preterm Parturient with Polyhydramnios and Pancreatitis: Primary Presentation of Hyperparathyroidism - Esther S. Han; Katherine Fritton; Phoebe Bacon; Martin K. Slodzinski; Cynthia Argani (Hindawi Limited, 2018)
Objective. To report a case of severe hypercalcemia secondary to primary hyperparathyroidism in a late-preterm pregnant patient and review medical and surgical treatments as well as obstetric and neonatal outcomes. Background. Diagnosis of parathyroid disease during pregnancy can be difficult due to nonspecific presentation. Management decisions are complex and require multidisciplinary collaboration. Case. A 29-year-old G2P1001 woman at 35 weeks and 3 days' gestation presented with preterm contractions, polyhydramnios, pancreatitis, and severe hypercalcemia. Work-up revealed primary hyperparathyroidism with multiple thyroid nodules. Patient history, presentation, and biopsy were suspicious for parathyroid carcinoma. Despite severe hypercalcemia, both patient and fetus remained stable and medical management was pursued in an attempt to optimize mother and fetus prior to delivery. Due to recalcitrant hypercalcemia, surgical resection was ultimately required. She was subsequently delivered in the setting of preterm labor. Final pathology revealed parathyroid adenoma with atypia and occult papillary thyroid carcinoma. Conclusion. Symptoms of hypercalcemia can mimic those of a normal third trimester pregnancy and can have serious maternal and fetal effects if left untreated. A coordinated, multidisciplinary approach to these patients is necessary.